Cambridge english for schools : - Littlejohn, Andrew (Cambridge University Press, 1996)
This book is the one of Cambridge English for School series which is the new approach to English. The series has 5 levels: Starter, levels 1-4. Every level consists of Student’s book, workbook, workbook cassette, teacher's book, class cassette, test, test cassette and video